Pasien laki-laki 14 Tahun dengan Hemoptysis ec TB Paru - Hazma Wildani Hasibuan; Elli Kusmayanti (Jurnal Medika Nusantara, 2024)
Tuberculosis is a direct infectious disease caused by the TB germ. The clinical features of pulmonary tuberculosis in children vary and are often related to the age of onset of the disease. Pulmonary tuberculosis should be suspected in children who show symptoms and have a history of exposure to tuberculosis in the home environment. This case report was obtained from primary data through history taking, physical examination and supporting examination. The male patient aged 14 years and 7 months came with a complaint of bloody cough 8 days before admission. The patient was referred from PMI Hospital to the emergency room of Cut Meutia Hospital with complaints of coughing with blood since 8 days smrs. Cough was complained occasionally and accompanied by phlegm in the last 2 months. The patient complained of fever that had been felt since 3 weeks ago. History of complete TB treatment and a history of contact with TB patients. Physical examination found additional breath sounds of rhonki and wheezing in both lung fields and thorax X-rays with the impression of active pulmonary TB. The management given is 2RHZ + 4RH OAT therapy given for 6 months, 2 months intensive, 4 months follow-up and symptomatic therapy.